2021
DOI: 10.1128/mbio.03634-20
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics Based on Comparative Genomics of Pathogenic Escherichia coli Lineages Harboring Polyketide Synthase ( pks ) Island

Abstract: The genotoxin colibactin is a secondary metabolite produced by the polyketide synthase (pks) island harbored by extraintestinal pathogenic E. coli (ExPEC) and other members of the Enterobacteriaceae that has been increasingly reported to have critical implications in human health. The present study entails a high-throughput whole-genome comparison and phylogenetic analysis of such pathogenic E. coli isolates to gain insights into the patterns of distribution, horizontal transmission, and evolution of the islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…Notably, the pks island was identified in extraintestinal pathogenic E. coli but has also been found in other members of the family Enterobacteriaceae ( Klebsiella pneumoniae , Enterobacter aerogenes , and Citrobacter koseri ). The pks genomic island phylogeny indicated horizontal acquisition/transmission and the possibility of exchange between compatible E. coli subtypes [ 123 ].…”
Section: Colibactin-producing E Coli In the Intestinal Microbiotamentioning
confidence: 99%
“…Notably, the pks island was identified in extraintestinal pathogenic E. coli but has also been found in other members of the family Enterobacteriaceae ( Klebsiella pneumoniae , Enterobacter aerogenes , and Citrobacter koseri ). The pks genomic island phylogeny indicated horizontal acquisition/transmission and the possibility of exchange between compatible E. coli subtypes [ 123 ].…”
Section: Colibactin-producing E Coli In the Intestinal Microbiotamentioning
confidence: 99%
“…The pks island is present in pathogenic, commensal, and even probiotic bacterial strains [ 24 ]. Large-scale whole-genome-based studies have investigated the pks island phylogeny and suggested the possibility of horizontal acquisition/transmission and exchange between compatible E. coli subtypes [ 42 ].…”
Section: Bacterial Genotoxinsmentioning
confidence: 99%
“…Our previous observations demonstrated high numbers of AMR genes as a part of genomic investigations of globally distributed and epidemiologically successful sequence types (STs) of E. coli such as ST131, ST38, ST405, and ST648 [ 4 ]. In another study, we observed that E. coli isolates that carry the genotoxin encoding pks island displayed lower phenotypic AMR as well as lower prevalence of AMR genes (especially the specific AMR determinants such as target inactivation/modification genes) [ 18 ].…”
Section: Different Mechanisms Employed By Mdr Pathogensmentioning
confidence: 99%